It’s the Taking Part that Counts? Participation, Performance and External Labour Market Conditions - Forde, Chris; Slater, Gary; Spencer, David (Relations industrielles / Industrial Relations, 2006)
This paper examines the relationship between participation, performance and the external labour market, using data from the 1998 British Workplace Employment Relations Survey. Our results show that participation can have positive productivity effects, particularly when practices are implemented alongside individual and organizational supports. Yet, we also find that the effects of participation are sensitive to external labour market conditions. In establishments adopting participation in a relatively piecemeal fashion, the positive association between participation and productivity depends upon the presence of relatively high unemployment, suggesting that ‘fear’ and ‘threat’ play an important role in generating high productivity in these establishments. The results do not rule out the possibility that some of the gains from participation stem from higher work intensity, rather than simply increased levels of commitment.